Occupational and Environmental Risk Factors for Contact Dermatitis among Industrial Workers in Karawang, Indonesia: A Cross-Sectional Study - Suryani, Febria; Iting Shofwati (Scientific Journal of Dermatology and Venereology, 2023)
Introduction: Contact dermatitis is a prevalent occupational skin disease, particularly among industrial workers exposed to various irritants and allergens. This study aimed to investigate the prevalence of contact dermatitis and identify occupational and environmental risk factors among industrial workers in Karawang, Indonesia. Methods: A cross-sectional study was conducted among 450 industrial workers in Karawang, Indonesia. Data were collected using a structured questionnaire, including demographics, occupational history, and environmental exposures. Dermatological examinations were performed to diagnose contact dermatitis. Descriptive statistics, chi-square tests, and logistic regression analysis were used to analyze the data. Results: The prevalence of contact dermatitis among the industrial workers was 22.4%. The most common type was irritant contact dermatitis (75%). Significant risk factors identified included exposure to solvents (OR = 3.2, 95% CI: 1.8-5.7), detergents (OR = 2.5, 95% CI: 1.4-4.5), and metalworking fluids (OR = 2.1, 95% CI: 1.2-3.7). Longer duration of employment (OR = 1.2, 95% CI: 1.1-1.4) and poor personal protective equipment (PPE) use (OR = 2.8, 95% CI: 1.6-4.9) were also associated with increased risk. Conclusion: Contact dermatitis is a significant occupational health problem among industrial workers in Karawang, Indonesia. Exposure to specific chemicals, longer duration of employment, and inadequate PPE use contribute to the increased risk. Implementing preventive measures, including proper PPE use, workplace hygiene, and health education programs, is crucial to reducing the burden of contact dermatitis in this population.